Penentuan Jumlah Pohon Contoh Minimal untuk Penyusunan Persamaan Volume Melalui Fungsi Taper: Studi Kasus pada Jenis Pinus Merkusii Jungh Et De Vriese di Hutan Pendidikan Gunung Walat, Sukabumi, Jawa Barat - M Muhdin; Arif Rakhman Hakim (Institut Pertanian Bogor (IPB University), 2004)
The study departs from the fact that the most difficult activity in constructing tree volume table is measurement of diameter and length of section of standing sample trees. Besides, the number of sample trees to represent the population is also another problem. This study examines the construction of the volume equation through taper function by reducing the quantity of sample trees. Validation was also conducted for testing the accuracy of such volume equation. The study found that the best taper function was the third order polynomial model i.e., d/D=f(h/H),(h/H)2,(h/H)3. The volume equation, constructed using only three sample trees by such taper function (V=0.3573337D2H), has almost the same good performance to equivalent the best model (V=6.14 10-5D1.8249H1.0342), that was constructed using 30 sample tree.Key words: taper function, tree volume equation, validation, accuracy, precision",